2019
DOI: 10.1111/obr.12948
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of healthy and unhealthy food and beverage price promotions and their potential influence on shopper purchasing behaviour: A systematic review of the literature

Abstract: Policies to restrict unhealthy food and beverage price promotions have been recommended, as part of a broader strategy to reduce obesity, but little evidence underpins such recommendations. We aimed to synthesize the literature on the prevalence of healthy and unhealthy food and beverage price promotions and their potential influence on purchasing behaviour. Eight scientific databases (covering health, business, and marketing) and grey literature were systematically searched using search terms related to "food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 24 publications
3
112
0
2
Order By: Relevance
“…Findings regarding the impact of price promotions and product placement on consumer behavior are consistent with findings of previous reviews [ 3 , 9 , 20 , 21 ]. To the authors’ knowledge, the review by Glanz et al is the only study to also explore promotion; however, they did not identify any studies related to signage, and only one related to in-store sampling [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Findings regarding the impact of price promotions and product placement on consumer behavior are consistent with findings of previous reviews [ 3 , 9 , 20 , 21 ]. To the authors’ knowledge, the review by Glanz et al is the only study to also explore promotion; however, they did not identify any studies related to signage, and only one related to in-store sampling [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…A review of price promotions among Scottish retailers found that TPR are the most prevalent form of price promotion, accounting for 74% of promotions, followed by bundle deals, which represent 23% of promotions [ 9 ]. Price promotions are offered more frequently for unhealthy compared to healthy products [ 2 , 3 , 5 , 7 , 8 , 9 , 20 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations